Polymer, pole piece and related battery monomer, battery and electric device

CN119654716APending Publication Date: 2025-03-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380056612.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-01-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The active material in the existing battery pole pieces has poor liquid storage capacity, resulting in poor battery cycle performance. In particular, the electrolyte is easily squeezed out under external squeezing force, resulting in capacity fading.

Method used

A polymer is used to form a gel state by standing with a solvent at a specific temperature and filtering to improve the wetting performance and liquid storage capacity of the electrolyte. The mutual attraction and physical combination of the polymer molecular chain and the electrolyte form a Gel in situ to lock in electrolyte.

Benefits of technology

The cycle performance and storage performance of the battery pole pieces are improved, the wetting performance of the electrolyte on the active material layer is enhanced, the difficulty of sucking back the electrolyte is reduced, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654716A_ABST
    Figure CN119654716A_ABST
Patent Text Reader

Abstract

The invention provides a polymer, a pole piece, a related battery monomer, a battery and an electric device. Adding the polymer into a first solvent at a first temperature to form a polymer system; after the polymer system is stood for 8 hours at the first temperature and is stood for more than or equal to 24 hours at the second temperature, a first substance is left after the polymer system is filtered by a 200-mesh filter screen, the first temperature is higher than the second temperature, the mass of the polymer is n, and the unit of the polymer is g; the mass of the first substance is m, and the unit of the first substance is g; and m / n of the polymer and the first substance is more than or equal to 5 and less than or equal to 1000. When the polymer is applied to a battery monomer, the cycle performance of the battery monomer can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Polymers, pole pieces and related battery cells, batteries and electrical devices Technical Field

[0001] The present application relates to the field of batteries, and in particular to a polymer, a pole piece and related battery cells, batteries and electrical devices. Background Art

[0002] Battery cells have the characteristics of high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes and power tools, etc.

[0003] As battery applications expand, the performance requirements for battery cells are becoming increasingly stringent. To improve the safety of battery cells, optimization and improvement of the electrode performance within the cells are common. However, the active material in the electrode currently has poor liquid storage capacity, resulting in poor cycling performance when used in battery cells.

[0004] Summary of the Invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a polymer, a pole piece and related battery cells, batteries and electrical devices.

[0006] The first aspect of the present application provides a polymer for use in a battery cell. The polymer is added to a first solvent at a first temperature to form a polymer system. After the polymer system is allowed to stand at the first temperature for 8 hours and at a second temperature for ≥24 hours, the polymer system is filtered through a 200-mesh filter, leaving a first substance. The first temperature is greater than the second temperature. The mass of the polymer is n, in g; the mass of the first substance is m, in g. The polymer and the first substance satisfy the following relationship: 5 ≤ m / n ≤ 1000. When the polymer meets these conditions, the cycling performance and storage performance of the battery cell can be further improved.

[0007] Therefore, the polymer of the present application can achieve molecular chain stretching within the higher safe operating temperature range of the secondary battery, promote the mutual attraction and physical bonding between the polymer molecular chain and the solvent in the electrolyte, which is beneficial to the bonding of the polymer molecular chain and the solvent, thereby storing the electrolyte in the active material layer; the polymer may not be mobile within the lower safe operating temperature range of the secondary battery, and the polymer can remain attached to the surface of the active material and lock the electrolyte in the spatial environment where the polymer is located, thereby improving the liquid storage capacity of the active material layer, and the electrolyte has good wetting performance on the active material layer, thereby improving the cycle performance of the secondary battery using the polymer.

[0008] In some embodiments, 10≤m / n≤1000; further optionally, 10≤m / n≤50. When the polymer meets the above conditions, the cycle performance and storage performance of the battery cell can be further improved.

[0009] In some embodiments, the first solvent comprises a cyclic carbonate solvent and / or a linear carbonate solvent;

[0010] Optionally, the cyclic carbonate solvent includes one or more of ethylene carbonate EC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC and dioctyl carbonate CC;

[0011] Optionally, the linear carbonate solvent includes one or more of dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, diphenyl carbonate DPC, methyl allyl carbonate MAC and polycarbonate VA.

[0012] In some embodiments, the crystallinity of the polymer measured by differential scanning calorimetry is X C %,0<X C ≤30; the melting temperature of the polymer is Tm, the unit is ℃, 0<Tm≤140.

[0013] Therefore, in the present application, since the polymer and the electrolyte in the battery cell have good affinity, the solvent in the electrolyte can quickly diffuse between the molecular chains of the polymer and be wrapped by the molecular chains, and can form an in-situ gel on the surface of the active material, thereby improving the wetting performance of the electrolyte on the active material layer, thereby improving the overall liquid absorption speed of the active material layer, and thus improving the cycle performance of the battery cell using the electrode.

[0014] In some embodiments, the glass transition temperature of the polymer is Tg, expressed in degrees Celsius, where -150 ≤ Tg ≤ 60. A relatively low glass transition temperature of the polymer results in greater segmental flexibility in the molecular chain, making it easier for adjacent molecular chains to be opened and for in-situ gel formation to occur. This improves the wettability of the active material layer with the electrolyte, thereby enhancing the cycling performance of the battery cell.

[0015] In some embodiments, the polymer comprises at least one of the structural units represented by formula (I) to the structural units represented by formula (III),

[0016] In formula (I) and formula (II), R1, R2, R3, and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group, and at least one of R1, R2, R3, and R4 includes a fluorine atom; if substituted, the substituent includes a fluorine atom. In formula (III), R5 includes a single bond, a substituted or unsubstituted C1-C3 alkyl group; if substituted, the substituent includes a fluorine atom. p is a positive integer selected from 1 to 3. n is a positive integer selected from 1,000 to 30,000.

[0017] The monomers used in the above-mentioned polymers are all short-chain monomers, which are conducive to the polymerization to form straight-chain linear structures or short-chain branched structures. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, thereby further improving the liquid storage capacity of the active substance.

[0018] In some embodiments, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C2 alkyl group or a substituted or unsubstituted C1-C2 alkoxy group; further optionally, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, a fluoromethyl group, a methoxy group or a perfluoromethoxy group.

[0019] In some embodiments, the polymer includes at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-11),

[0020] In some embodiments, the polymer includes at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-5),

[0021] In some embodiments, the polymer includes at least one of the structural units represented by formula (III-1) to the structural units represented by formula (III-3),

[0022] In some embodiments, n is a positive integer selected from 5000 to 20000; and / or the molecular weight of the polymer is 2×10 5 g / mol to 1.5×10 6When the polymer molecular weight is within the above range, it can ensure a certain solubility of the polymer in the electrolyte while being difficult to be completely dissolved and dispersed by the electrolyte, which is beneficial for regulating the distribution and dispersion of the polymer on the surface of the active material. It can also further improve the flexibility between the polymer molecular chains. The interaction between the molecular chains is relatively weak, which facilitates the solvent molecules in the electrolyte to open the molecular chains, enter between the molecular chains, and be wrapped by the molecular chains. This facilitates the entry of active ions into the active material through the solvent, achieving smooth and rapid migration of active ions.

[0023] The second aspect of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer arranged on the positive electrode collector, the positive electrode film layer includes a positive electrode active material and a polymer, and the polymer includes the polymer described in any embodiment of the first aspect of the present application.

[0024] The third aspect of the present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer arranged on the negative electrode current collector, the negative electrode film layer includes a negative electrode active material and a polymer, and the polymer includes the polymer described in any embodiment of the first aspect of the present application.

[0025] The fourth aspect of the present application provides a battery cell, which includes a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet includes the positive electrode sheet as described in any embodiment of the second aspect of the present application; and / or the negative electrode sheet includes the negative electrode sheet as described in any embodiment of the third aspect of the present application.

[0026] A fifth aspect of the present application provides a battery comprising the battery cell as described in the fourth aspect of the present application.

[0027] The sixth aspect of the present application provides an electrical device comprising the battery as described in the fifth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0029] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.

[0030] FIG. 2 is an exploded schematic diagram of an embodiment of the battery cell of FIG. 1 .

[0031] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.

[0032] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.

[0033] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .

[0034] FIG6 is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.

[0035] The drawings are not necessarily drawn to scale.

[0036] The following are the descriptions of the reference numerals:

[0037] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;

[0038] 5. Battery cell; 51. Housing; 52. Electrode assembly;

[0039] 53. Cover plate;

[0040] 6. Electrical equipment. DETAILED DESCRIPTION

[0041] The following detailed description specifically discloses the embodiments of the polymer, electrode, and related battery cells, batteries, and electrical devices of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0042] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0043] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0044] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.

[0045] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.

[0046] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0047] In this application, the terms "plurality" and "multiple" refer to two or more.

[0048] The term "alkyl" encompasses both straight and branched chain alkyl groups. For example, the alkyl group may be a C1-C5 alkyl group, a C1-C4 alkyl group, a C1-C3 alkyl group, or a C1-C2 alkyl group. In some embodiments, the alkyl group includes a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, and the like. Additionally, the alkyl group may be optionally substituted. When substituted, the substituent includes a fluorine atom.

[0049] The term "alkoxy" refers to a group in which an alkyl group is connected to an oxygen atom by a single bond. For example, the alkoxy group can be a C1 to C5 alkoxy group, a C1 to C3 alkoxy group, or a C1 to C2 alkoxy group. In some embodiments, the alkoxy group can include a methoxy group, an ethoxy group, or a propoxy group. In addition, the alkoxy group can be optionally substituted.

[0050] The term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom or the like.

[0051] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).

[0052] The secondary battery includes a positive electrode sheet, a negative electrode sheet and an electrolyte. The electrolyte infiltrates the positive electrode sheet and the negative electrode sheet, thereby achieving smooth migration of active ions between the positive electrode sheet and the negative electrode sheet.

[0053] The electrode sheet (such as the positive electrode sheet and / or the negative electrode sheet) includes a current collector and an active material layer arranged on at least one surface of the current collector. The active material layer includes a pore structure. The electrolyte diffuses from the surface of the active material through the pore structure into the active material layer, thereby making the active material layer infiltrated with the electrolyte, and the active ions can smoothly migrate from the positive electrode sheet to the negative electrode sheet.

[0054] The inventors discovered that active material layers typically contain highly crystalline polymers, such as polyvinylidene fluoride (PVDF). PVDF can bond the active material to the current collector, providing adhesion and support for the electrode. However, active material layers containing such polymers often exhibit poor electrolyte affinity, resulting in poor electrolyte wettability and poor liquid storage capacity. During use, transportation, or module assembly, secondary batteries may be subject to external compressive forces that squeeze the electrolyte from the active material layer. This compressive force gradually hinders electrolyte reabsorption, leading to capacity decay and deteriorating battery cycle performance.

[0055] In view of this, the inventors improved the performance of the polymer in the electrode from the perspective of improving the liquid storage capacity of the electrode, increased the affinity between the polymer and the electrolyte, and improved the wetting performance of the electrolyte on the electrode, thereby improving the cycle performance of the secondary battery using the polymer.

[0056] polymer

[0057] In the first aspect, the present application proposes a polymer. The polymer is applied to a battery cell, and the polymer is added to a first solvent at a first temperature to form a polymer system; the polymer system is allowed to stand for 8 hours at the first temperature and for ≥24 hours at a second temperature, and after undergoing two stages of standing treatment, the polymer system is partially transformed in situ into a gel-state substance, and then the polymer system is filtered through a 200-mesh filter to leave a first substance, wherein the first temperature is greater than the second temperature. After the polymer system is filtered through a 200-mesh filter, the mobile phase solvent is filtered out, and the remainder, namely the first substance, is retained. The mass of the polymer is n, and its unit is g; the mass of the first substance is m, and its unit is g; the polymer and the first substance satisfy: 5≤m / n≤1000; optionally, 10≤m / n≤1000; further optionally, 10≤m / n≤50. Illustratively, m / n may be 5, 10, 20, 25, 28, 30, 32, 35, 40, 50, 80, 100, 200, 500, 1000, or a range consisting of any two of the foregoing values.

[0058] Illustratively, based on the mass of the polymer system, the ratio of the mass content of the polymer to the mass content of the first solvent ranges from 1:100 to 1:10, for example, 3:50.

[0059] Exemplarily, the first solvent is the same as or similar to the solvent of the electrolyte, and the first solvent may include a carbonate solvent, for example, a carbonate solvent including a cyclic carbonate solvent and / or a linear carbonate solvent.

[0060] As examples of the cyclic carbonate solvent, the cyclic carbonate solvent includes one or more of ethylene carbonate EC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC.

[0061] As examples of the linear carbonate solvent, the linear carbonate solvent includes one or more of dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, diphenyl carbonate DPC, methyl allyl carbonate MAC, and polycarbonate VA.

[0062] Optionally, the first solvent may also contain a lithium salt and an electrolyte additive, such as lithium hexafluorophosphate, vinylene carbonate VC, fluorovinylene carbonate FEC, and the like.

[0063] In this application, m / n is also referred to as the precipitation value, which characterizes the ability of the polymer and solvent to transform into a gel-state substance.

[0064] The first substance mainly includes a gel-state substance formed by a polymer and a first solvent. In this type of gel-state substance, the molecular structure of the polymer basically does not change.

[0065] In some embodiments, the first substance is dried at 80° C. for 12 hours to remove the first solvent in the first substance. Detection by infrared spectrophotometry IR or nuclear magnetic resonance NMR testing shows that the main component of the first substance after drying is the polymer described above.

[0066] In the present application, the glass transition temperature of the polymer is ≤ the first temperature ≤ the melting temperature of the polymer, and the first temperature is the normal use temperature of the battery cell.

[0067] The first temperature is greater than the second temperature. The first temperature and the second temperature can be set to a safe operating temperature range of the battery cell. For example, the first temperature can be 60°C to 80°C, such as 70°C, and the second temperature can be -30°C to 30°C, such as 25°C. That is, the first temperature is the higher operating temperature of the battery cell, and the second temperature is approximately room temperature or low temperature.

[0068] The polymer can achieve molecular chain stretching within the higher safe operating temperature range of the secondary battery, promote the mutual attraction and physical bonding between the polymer molecular chain and the solvent in the electrolyte, which is beneficial to the bonding of the polymer molecular chain and the solvent, thereby storing the electrolyte in the active material layer; the polymer may not be mobile within the lower safe operating temperature range of the secondary battery, and the polymer can remain attached to the surface of the active material and lock the electrolyte in the spatial environment where the polymer is located, thereby improving the liquid storage capacity of the active material layer, and the electrolyte has good wetting performance on the active material layer, thereby improving the cycle performance of the secondary battery using the polymer.

[0069] By increasing the temperature, this application can achieve stretching of the polymer molecular chains within the safe operating temperature range of the battery cells, promoting mutual attraction and physical bonding between the polymer molecular chains and the solvent. At room temperature, the activity of the polymer molecular segments decreases, maintaining adhesion to the surface of the active material and locking the electrolyte in the spatial environment of the polymer, forming a state similar to in-situ gel, increasing the liquid storage capacity of the active material and improving cycle performance.

[0070] After further research, the inventors found that when the polymer also meets one or more of the following conditions, the cycle performance of the battery cell can be further improved.

[0071] In some embodiments, the crystallinity of the polymer measured by differential scanning calorimetry is X C %,0<X C ≤30; the melting temperature of the polymer is Tm, the unit is ℃, 0<Tm≤140.

[0072] Crystallization refers to the process in which atoms, ions or molecules in a material are arranged in a certain spatial order to form an orderly structure. The conformation of the polymer in the crystallization is determined by both intramolecular and intermolecular factors. The intermolecular force will affect the packing density between molecular chains. C % is used to characterize the degree of crystallinity in the material, which can be measured by differential scanning calorimetry (DSC). Specifically, the test steps are: take 0.5g to 0.8g of sample, place the sample in a carrier crucible, and perform temperature raising and lowering treatment on the sample in a nitrogen atmosphere, heating the sample at a rate of 10℃ / min from an initial temperature 20℃ lower than the intrinsic Tg of the material to a cutoff temperature 20℃ higher than the intrinsic Tm of the material, and determine the actual glass transition temperature Tg and melting temperature Tm of the material based on the endothermic and exothermic peak or transition point of the material in the process.

[0073] Compared to the fluorinated polymers commonly used in secondary batteries in related technologies, which have relatively high crystallinity and melting temperatures, the polymers have good resistance to liquid electrolytes, thereby effectively providing long-term adhesion or rebound suppression effects on active materials during battery use. The fluorinated polymers used in this application have relatively low crystallinity and melting temperatures, resulting in a loose arrangement of molecular chains, low forces between molecular chains, and easy uncoupling of adjacent molecular chains. Chain segment motion is achieved through intermolecular rotation, forming a highly flexible molecular chain structure.

[0074] Because the polymer and the electrolyte in the battery cell have good affinity, the solvent in the electrolyte can quickly diffuse between the molecular chains of the polymer and be wrapped by the molecular chains. It can form an in-situ gel on the surface of the active material and adhere to the surface of the active material to protect the active material. This closely connects the active material and the electrolyte, improves the solid-liquid interface performance, reduces the side reactions between the active material and the electrolyte, and improves the cycle performance of the battery cell.

[0075] For example, the crystallinity X of the polymer measured by differential scanning calorimetry is C % can be 5%, 10%, 15%, 20%, 25%, 30% or a range consisting of any two of the above values.

[0076] For example, the melting temperature of the polymer may be 10°C, 20°C, 50°C, 70°C, 90°C, 100°C, 120°C, 140°C, or a range consisting of any two of the foregoing values.

[0077] In some embodiments, the glass transition temperature of the polymer is Tg, which is expressed in °C, and is -150≤Tg≤60.

[0078] The glass transition temperature is the temperature at which the chain segments of a polymer transition from freezing to movement. The glass transition temperature has a certain influence on the flexibility of the polymer molecular chain. The lower the glass transition temperature, the better the flexibility of the polymer molecular chain at room temperature. The higher the glass transition temperature, the worse the flexibility of the molecular chain at room temperature. The glass transition temperature can be measured by differential scanning calorimetry (DSC). The glass transition temperature of a polymer is relatively low, the segment flexibility of the molecular chain is better, and adjacent molecular chains are easier to open. For example, the glass transition temperature of a fluoropolymer can be -150°C, -140°C, -120°C, -100°C, -80°C, -60°C, -30°C, 0°C, 30°C, 60°C, or a range consisting of any two of the above values.

[0079] In some embodiments, the polymer comprises at least one of the structural units represented by formula (I) to the structural units represented by formula (III),

[0080] In formula (I) and formula (II), R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and at least one of R1, R2, R3 and R4 includes a fluorine atom; when substituted, the substituent includes a fluorine atom.

[0081] In formula (III), R5 includes a single bond, a substituted or unsubstituted C1-C3 alkyl group; when substituted, the substituent includes a fluorine atom.

[0082] p is a positive integer selected from 1 to 3.

[0083] n is a positive integer selected from 1,000 to 30,000.

[0084] In some embodiments, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C2 alkyl group, or a substituted or unsubstituted C1-C2 alkoxy group, and at least one of R1, R2, R3 and R4 includes a fluorine atom.

[0085] In some embodiments, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, a fluoromethyl group, a methoxy group or a perfluoromethoxy group.

[0086] In some embodiments, the polymer includes at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-11),

[0087] Optionally, the polymer includes at least two of the structural units represented by formula (I-1) to the structural units represented by formula (I-11).

[0088] In some embodiments, the polymer includes at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-5),

[0089] In some embodiments, the polymer includes at least one of the structural units represented by formula (III-1) to the structural units represented by formula (III-3),

[0090] Exemplarily, the polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), perfluoroalkoxy polymer (PFA), perfluoropolyether (PFPE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE) and perfluoro (1-butenyl vinyl ether) polymer (CYTOP for short).

[0091] Optionally, the polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE).

[0092] The above polymer may be derived from one or more of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene and pentafluoropropylene. Alternatively, the above fluorinated polymer may be derived from at least two of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene and pentafluoropropylene.

[0093] The monomers used in the above-mentioned polymers are all short-chain monomers, which are conducive to the polymerization to form straight-chain linear structures or short-chain branched structures. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, thereby further improving the interfacial properties of the active substance.

[0094] The groups of the polymers of the present application can be detected by infrared spectrophotometry IR. Specifically, the polymers are tested using a Thermo Nicolet Nexus 670 attenuated total reflectance Fourier transform infrared spectrometer (FTIR-ATR), and then tested in accordance with the standard GB / T6040-2002. The test range is: ATR method 600-4000 cm -1 ; Repeatability: ±2cm -1 ; Resolution: better than 4cm -1 ; Transmission depth 0.2~0.6μm.

[0095] The structure of the polymer of the present application can be tested by nuclear magnetic resonance (NMR). Specifically, 1H NMR and 13C NMR are performed on a Varian Mercury Plus-400 NMR spectrometer at a test temperature of 20° C., TMS as an internal standard, CDCl 3 as a solvent, and a proton resonance frequency of 400 MHz.

[0096] In some embodiments, n is a positive integer selected from 5,000 to 20,000.

[0097] In some embodiments, the molecular weight of the polymer is 2×10 5 g / mol to 1.5×10 6 g / mol.

[0098] When the molecular weight of the polymer is within the above range, it can ensure that the polymer exhibits a certain solubility in the electrolyte, while not being easily completely dissolved and dispersed by the electrolyte, which is conducive to regulating the distribution and dispersion of the polymer on the surface of the active material; and it can further improve the flexibility between the molecular chains of the polymer. The interaction force between the molecular chains is relatively weak, which is conducive to the solvent molecules in the electrolyte opening the molecular chains and entering between the molecular chains and being wrapped by the molecular chains. This is conducive to the active ions entering the active material through the solvent, realizing the smooth and rapid migration of the active ions. For example, the molecular weight of the polymer can be 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.

[0099] The molecular weight of a polymer is well known in the art and can be measured using equipment and methods commonly used in the art. Gel permeation chromatography (GPC) testing can be used. The specific testing steps are as follows: take an appropriate amount of the sample to be tested (the sample concentration is sufficient to ensure 8%-12% shading), add 20 ml of deionized water, and simultaneously operate externally for 5 minutes (53 KHz / 120 W) to ensure that the sample is completely dispersed. Then, the sample is measured in accordance with GB / T19077-2016 / ISO 13320:2009 standard.

[0100] Alternatively, a multi-angle laser light scattering (MALLS) instrument was used for testing. Specifically, a GPC coupled with a Dawn Heleos II multi-angle laser light scattering device, an Optilab T-rEX refractive index (RI) detector, and a Visco Star II viscometer (Wyatt Technology Corporation, USA) was used. Testing was conducted at 30°C, using tetrahydrofuran as the mobile phase at a flow rate of 1.0 ml / min. SEC-SAMLL data were processed using the commercial ASTRA6 software to obtain molecular weight parameters.

[0101] Positive electrode

[0102] In the second aspect, the present application proposes a positive electrode plate; the positive electrode plate includes a positive electrode collector and a positive electrode film layer arranged on the positive electrode collector, the positive electrode film layer includes a positive electrode active material and a polymer, and the polymer includes the polymer described in any embodiment of the first aspect of the present application.

[0103] For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0104] The pole piece can be made by coating a slurry on a current collector, drying it, and cold pressing it. Alternatively, the pole piece can be made from a battery cell. The battery cell is disassembled, and the pole piece soaked in electrolyte is removed from the battery cell. The pole piece soaked in electrolyte is then placed under vacuum drying at 100°C for 12 hours to obtain the pole piece, which can be used for pole piece testing such as liquid absorption rate.

[0105] Polymers can be synthesized through emulsion polymerization, suspension polymerization, bulk polymerization, solution polymerization, and other methods. Alternatively, the polymer can be derived from a battery cell. The battery cell is disassembled, and the electrode, which is immersed in the electrolyte, is removed. The active material of the electrode is then peeled off from the current collector by external force to form a powder sample. This powder is then added to dimethyl carbonate (DMC) and stirred at 80°C for 8 hours at 500 rpm. After stirring, the mixture is allowed to stand at room temperature for 10 minutes. The supernatant is then dried at 80°C for 12 hours to obtain the polymer. The resulting polymer may contain a small amount of lithium salt, but this has little impact on infrared and precipitation value testing. To ensure the accuracy of the polymer, the lithium salt can be further separated by rinsing with DMC at room temperature.

[0106] In some embodiments, the positive electrode active material layer satisfies:

[0107]

[0108]

[0109] v / λ>1.00 Formula (3),

[0110] In formula (1) to formula (3),

[0111] λ represents the porosity of the active material layer;

[0112] P1 represents the actual compaction density of the positive electrode active material layer, and its unit is g / cm 3 ;

[0113] P2 represents the actual compaction density of the positive electrode active material, and its unit is g / cm 3 ;

[0114] v represents the liquid absorption rate of the positive electrode active material layer, and its unit is mg / s.

[0115] d represents the diameter of the capillary of the positive electrode active material layer in the capillary test, and its unit is mm;

[0116] h represents the height of the liquid level in the capillary tube, in mm;

[0117] ρ represents the density of the electrolyte in the capillary test, and its unit is g / cm 3 ;

[0118] t represents the time for the electrolyte to be absorbed in the capillary, and its unit is s.

[0119] In this application, the actual compaction density P1 refers to the ratio of the mass of the positive electrode active material layer per unit area in the electrode to its thickness. The actual compaction density is determined by the force of the roller pressing after the electrode is coated, and the unit is g / cm 3 The specific test steps are to take a certain area S of the electrode, weigh the mass M of its positive electrode active material layer, and measure the thickness D of the positive electrode active material layer. The actual compaction density = M / (S×D).

[0120] In this application, the true compaction density P2 refers to the density of the positive electrode active material itself in the positive electrode active material layer; specifically, it refers to the mass of the unit "actual volume of solid material (excluding open pores, closed pores and pores between particles)" in a dense state. The true volume V is obtained by testing, and then the true compaction density is obtained according to P=m / V. The test can be carried out in accordance with GB / T24586-2009; specifically, the test steps are as follows:

[0121] 1) Pretreatment: Place a clean and dry sample cup on a balance, reset it to zero, add the powder sample to the cup, filling it to about 1 / 2 of the cup volume, and record the sample mass.

[0122] 2) Place the sample cup containing the sample in the true density tester, seal the test system, and introduce helium according to the program. By detecting the pressure of the gas in the sample chamber and expansion chamber, the true volume is calculated according to Bohr's law (PV=nRT), and thus the true compacted density is calculated.

[0123] Among them, the volume of the sample cup is: 3.5cm 3 ;Analytical gas: helium.

[0124] Formula (1) can be used to calculate the porosity λ of the active material layer through the actual compaction density and the true compaction density.

[0125] Specifically,

[0126] Wherein, V1 represents the volume of the positive electrode active material layer under mass m, and its unit is cm 3 ;

[0127] V2 represents the volume occupied by active particles in the positive electrode active material layer under mass m, and its unit is cm 3 ;

[0128] m represents the mass of the positive electrode active material layer, and its unit is g.

[0129] Formula (2) can represent the speed at which a certain point of the electrode completely absorbs the liquid (e.g., electrolyte) in the capillary per unit time. In this application, a certain point of the electrode refers to an area of ​​the electrode with a certain area, and its area corresponds to the cross-sectional area of ​​the capillary.

[0130] In this application, the method for detecting the liquid absorption rate of the electrode comprises the following steps:

[0131] A predetermined amount of electrolyte is drawn by a capillary tube;

[0132] The capillary is brought into contact with the electrode, and the electrode to be tested absorbs the electrolyte in the capillary under capillary action;

[0133] After a predetermined time t, the liquid level h of the electrolyte absorbed in the capillary is recorded, and the amount of electrolyte absorbed is calculated based on the liquid level h and diameter d of the capillary and the density ρ of the electrolyte. The liquid absorption rate v of the electrode is quantitatively calculated based on the ratio of the absorbed amount and the predetermined time t.

[0134] Exemplarily, d takes a value of 0.2 to 1, for example, a value of 0.2; h takes a value of 3 to 5, for example, a value of 3.

[0135] The capillary tube has capillary channels that allow it to directly absorb electrolyte through capillary action, without the need for an external drive unit to provide suction power. This allows, on the one hand, more precise control of the amount of electrolyte absorbed through capillary action; on the other hand, because the electrode absorbs electrolyte through its own capillary action, the electrode only draws electrolyte from the capillary tube when the capillary tube contacts the electrode under test. When contact is broken, the electrolyte in the capillary tube stops flowing. Therefore, the amount of electrolyte absorbed in the capillary tube accurately reflects the amount of electrolyte absorbed by the electrode, further improving the accuracy of the test results and enabling quantitative calculation of the electrode's absorption rate.

[0136] Formula (3) represents the liquid absorption rate of the electrode under the porosity λ, which can be used to characterize the liquid absorption speed of the electrode.

[0137] The polymer of the present application is introduced during the preparation process of the active material layer, which can form uniform high wetting points inside the active material layer, uniformly improve the wetting performance of the active material layer, thereby increasing the overall liquid absorption speed of the active material layer, thereby improving the cycle performance of the battery cell using the electrode.

[0138] Optionally, 1.00<v / λ<50.00.

[0139] In some embodiments, 1.00 < v / λ < 4.00; alternatively, 1.20 ≤ v / λ ≤ 3.80; further alternatively, 1.4 ≤ v / λ ≤ 3.6. For example, v / λ can be 1.20, 1.40, 1.80, 2.00, 2.50, 3.00, 3.50, 3.60, 3.80, 3.90, or a range consisting of any two of the above values.

[0140] In some embodiments, based on the mass of the positive electrode active material layer, the mass percentage of the polymer is A%, wherein 0.1≤A≤1.5.

[0141] When the polymer content by weight is within the above range, the interfacial properties of the positive electrode active material layer can be significantly improved. For example, the polymer content by weight can be 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, or a range consisting of any two of the above values.

[0142] The positive electrode film layer includes a positive electrode active material, and the positive electrode active material can be a positive electrode active material for a battery cell known in the art. As an example, the positive electrode active material may include at least one of the following materials: a layered positive electrode active material (such as ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich / sodium layered, and rock salt phase layered materials), an olivine-type phosphate active material, and a spinel-structured positive electrode active material (such as spinel lithium manganate, spinel lithium nickel manganate, lithium-rich spinel lithium manganate, and lithium nickel manganate, etc.).

[0143] For example, the general formula of the layered positive electrode active material is: Li x A y Ni a Co b Mn c M (1-a-b-c) Y z , wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A is selected from one or more of Na, K, and Mg; M is selected from one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; Y is selected from one or more of O and F. Optionally, y=0. Specifically, the layered structure positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2(NCM333),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811) and LiNi 0.5 Co 0.2 Mn 0.3 One or more of O2 (NCM523).

[0144] For example, the general formula of the olivine phosphate active material is: Li x A y Me a M b P 1-c X c Y z , wherein, 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A is selected from one or more of Na, K, and Mg; Me is selected from one or more of Mn, Fe, Co, and Ni; M is selected from one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X is selected from one or more of S, Si, Cl, B, C, and N; and Y is selected from one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.

[0145] For example, the general formula of the positive electrode active material of the spinel structure is: Li x A y Mn a M 2-a Y z , wherein 0≤x≤2, 0≤y≤1, and 0.9≤x+y≤2; 0.5≤a≤2; 3≤z≤5; A is selected from one or more of Na, K, and Mg; M is selected from one or more of Ni, Co, B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y is selected from one or more of O and F. Specifically, the positive active materials of the spinel structure include LiMn2O4, LiNi 0.5 Mn 1.5 O4、LiCr 0.3 Mn 1.7 O4、Li 1.1 Al 0.1 Mn1.9 O4, Li2Mn2O4 and Li 1.5 One or more of Mn2O4.

[0146] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil or an aluminum alloy foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include a combination of one or more selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material base layer may include a combination of one or more selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0147] In some embodiments, the positive electrode film layer may further optionally include a positive electrode conductive agent. This application does not particularly limit the type of positive electrode conductive agent. For example, the positive electrode conductive agent may include a combination of one or more selected from superconducting carbon, conductive carbon black, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is less than 5% based on the total mass of the positive electrode film layer.

[0148] In some embodiments, the positive electrode film layer may further optionally include a positive electrode binder. The present application does not particularly limit the type of positive electrode binder. As an example, the positive electrode binder may include a combination of one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode binder is less than 5%.

[0149] The positive electrode film is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying it, and cold pressing it. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0150] Negative electrode

[0151] In a third aspect, the present application proposes a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer arranged on the negative electrode current collector, the negative electrode film layer includes a negative electrode active material and a polymer, and the polymer layer includes the polymer described in any embodiment of the first aspect of the present application.

[0152] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0153] In some embodiments, the negative electrode active material layer satisfies:

[0154] v / λ>1.00 Formula (3),

[0155] In formula (1) to formula (3),

[0156] λ represents the porosity of the negative electrode active material layer;

[0157] v represents the liquid absorption rate of the negative electrode active material layer, and its unit is mg / s.

[0158] The detection methods of λ and v are as described for the positive electrode active material layer and will not be repeated here.

[0159] In some embodiments, 3.00<v / λ<50.00; alternatively, 3.40≤v / λ≤30.00. For example, v / λ can be 3.20, 3.40, 3.50, 4.00, 4.50, 5.00, 5.50, 6.00, 6.50, 7.00, 8.00, 9.00, 9.50, 10.00, 10.50, 11.00, 12.00, 13.00, 14.00, or a range consisting of any two of the above values.

[0160] In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage of the polymer is B%, wherein 0.2≤B≤5.0.

[0161] When the polymer content by weight is within the above range, the interfacial properties of the negative electrode active material layer can be significantly improved. For example, the polymer content by weight can be 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, or a range consisting of any two of the above values.

[0162] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0163] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0164] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The negative electrode binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0165] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0166] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0167] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the polymer, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0168] battery cells

[0169] In a fourth aspect, the present application provides a battery cell, comprising a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet. The battery cell may be a lithium-ion battery, for example.

[0170] In some embodiments, the positive electrode sheet may be the positive electrode sheet of any embodiment of the second aspect of the present application, thereby improving the cycle performance of the battery cell. The negative electrode sheet may be a conventional negative electrode sheet.

[0171] In other embodiments, the negative electrode plate may be any of the negative electrode plates of the third aspect of the present application, thereby improving the cycle performance of the battery cell. The positive electrode plate may be a conventional positive electrode plate.

[0172] In some further embodiments, the positive electrode plate can adopt the positive electrode plate of any embodiment of the second aspect of the present application, and the negative electrode plate can adopt the negative electrode plate of any embodiment of the third aspect of the present application, thereby improving the cycle performance of the battery cell.

[0173] [Electrolytes]

[0174] Battery cells also include an electrolyte, which conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte; it can be selected based on needs. For example, the electrolyte can be liquid, gel, or solid.

[0175] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0176] As an example, the lithium salt may include a combination of one or more selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0177] As an example, the organic solvent may include a combination of one or more selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0178] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0179] [Isolation film]

[0180] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0181] In some embodiments, the material of the separator can include a combination of one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.

[0182] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process or a lamination process.

[0183] The present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square or any other shape. FIG1 shows a battery cell 5 of a square structure as an example.

[0184] In some embodiments, as shown in Figures 1 and 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0185] The manufacturing method of the battery cell of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, separator, and negative electrode sheet can be wound or laminated to form an electrode assembly. The electrode assembly is then placed in an outer packaging, dried, and then injected with electrolyte. The battery cell is then vacuum packaged, allowed to stand, formed, and shaped to obtain a battery cell.

[0186] In some embodiments of the present application, the battery cells according to the present application can be assembled into a battery module. The battery module can contain multiple battery cells, and the specific number can be adjusted according to the application and capacity of the battery module.

[0187] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple battery cells 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 5 may be secured together using fasteners.

[0188] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.

[0189] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0190] Both the battery module 4 and the battery pack can be used as specific examples of the battery of this application.

[0191] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0192] Electrical devices

[0193] In a fifth aspect, the present application provides an electrical device, which includes at least one of the battery cells, battery modules, and battery packs of the present application. The battery cells, battery modules, and battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0194] The electric device can select a battery cell, battery module or battery pack according to its usage requirements. Figure 6 is a schematic diagram of an electric device as an example. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the electric device, a battery pack 1 or a battery module can be used. As another example, the electric device can be a mobile phone, a tablet computer, a laptop computer, etc. The electric device usually requires to be lightweight and thin, and a battery cell can be used as a power source.

[0195] Example

[0196] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0197] Example 1

[0198] (1) Preparation of positive electrode sheet:

[0199] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.

[0200] A positive electrode slurry is prepared by mixing a fluorinated polymer, the positive electrode active material LiFePO4, a conductive agent carbon black, a binder such as polyvinylidene fluoride (PVDF), and N-methylpyrrolidone (NMP). The mass ratio of fluorinated polymer, LiFePO4, conductive carbon black, PVDF, and N-methylpyrrolidone (NMP) in the positive electrode slurry is 0.5:96.8:2:0.5:0.2. The positive electrode slurry is coated on a current collector aluminum foil and dried at 85°C before cold pressing. The sheet is then trimmed, cut, and slit, and then dried under vacuum at 85°C for 4 hours to form the positive electrode sheet.

[0201] (2) Preparation of negative electrode sheet:

[0202] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.

[0203] Fluorinated polymer, artificial graphite (negative electrode active material), carbon black (conductive agent), styrene-butadiene rubber (SBR) (binder), sodium carboxymethyl cellulose (CMC) (thickener), and deionized water were mixed uniformly in a weight ratio of 2.5:94:0.5:2:1:100 to prepare the negative electrode slurry. The negative electrode slurry was coated on the current collector copper foil and dried at 85°C. After cold pressing, trimming, cutting, and slitting, the negative electrode sheet was dried at 120°C under vacuum for 12 hours.

[0204] (3) Preparation of electrolyte:

[0205] In an environment with a water content of less than 10ppm, the non-aqueous organic solvents ethylene carbonate EC and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 3:7 to obtain an electrolyte solvent. Subsequently, the lithium salt LiPF6 and the mixed solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0206] (4) Preparation of lithium-ion batteries:

[0207] A 16μm polyethylene film (PE) is used as a separator. The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrodes to provide insulation. The electrodes are then wound to form an electrode assembly. The electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte. The battery undergoes vacuum packaging, resting, formation, and shaping to produce a lithium-ion battery.

[0208] The data of the examples and comparative examples are shown in Table 1.

[0209] Test section

[0210] 1. Lithium-ion battery capacity retention test

[0211] The lithium-ion batteries prepared in the Examples and Comparative Examples were charged to 4.25V at room temperature using an equivalent 1.2C stepcharge. They were then charged at a constant voltage of 4.25V to a current of 0.05C, left for 5 minutes, and discharged at 0.33C to 2.8V. The resulting capacity was recorded as the initial capacity C0. The initial clamping force of the lithium-ion battery was set to 10,000 N. The above steps were repeated for the same battery, and the discharge capacity Cn of the battery after the nth cycle was recorded. The battery capacity retention rate after each cycle, Pn, = Cn / C0*100%. A graph of the battery capacity retention rate versus cycle number for the polymers in the Examples and Comparative Examples was generated, with the 200 points P1, P2, ..., P200 as the ordinate and the corresponding cycle number as the abscissa.

[0212] During this test, the first cycle corresponds to n=1, the second cycle corresponds to n=2, ..., and the 200th cycle corresponds to n=200. For example, the battery capacity retention data corresponding to Example 1 in Table 1 is the data measured after 200 cycles under the above test conditions, i.e., the P200 value. The testing process for Comparative Example 1 and the other examples is the same as above.

[0213] 2. Lithium-ion battery DC impedance test

[0214] The lithium-ion batteries prepared in the Examples and Comparative Examples were charged to 4.25V at 25°C using an equivalent 1.2C stepcharge. They were then charged to a current of 0.05C at a constant voltage of 4.25V. After 5 minutes of rest, the voltage V1 was recorded. The batteries were then discharged at 1 / 3C for 30 seconds, and the voltage V2 was recorded. The internal resistance DCR1 of the battery after the first cycle was calculated as (V2 - V1) / 1 / 3C. The above steps were repeated for the same battery, and the internal resistance DCRn of the battery after the nth cycle (n = 1, 2, 3, ..., 200) was recorded. The 200 points (DCR1, DCR2, DCR3, ..., DCR200) ​​were plotted as the ordinate, and the corresponding cycle number as the abscissa, to produce a graph of the discharge DCIR versus cycle number for the polymers in the Examples and Comparative Examples.

[0215] During this test, the first cycle corresponds to n=1, the second cycle corresponds to n=2, and so on, and the 200th cycle corresponds to n=200. For example, the internal resistance increase ratio of the battery in Example 1 in Table 1 = (DCRn - DCR1) / DCR1 * 100%. The testing procedures for Comparative Example 1 and the other examples are the same as above. The data in Table 1 were measured after 200 cycles under the above test conditions.

[0216] Test results

[0217] Table 1

[0218] In Table 1, VDF represents vinylidene fluoride, HFP represents hexafluoropropylene, and TFE represents tetrafluoroethylene. 90% VDF means that the molar percentage of VDF is 90% based on the total molar amount of VDF and HFP, and 10% FEP means that the molar percentage of FEP is 10%.

[0219] As shown in Table 1, compared to Comparative Example 1, the addition of the polymer of the present application to the positive and / or negative electrode sheets in the present embodiment improves the cycling performance of the lithium-ion battery. Compared to Comparative Example 2, when 5≤m / n≤1000 is satisfied, and particularly when 10≤m / n≤50, the molecular chains of the present embodiment tend to be loosely arranged, the interaction between the molecular chains is small, adjacent molecular chains are easily opened, and segmental motion is achieved through intermolecular internal rotation, forming a highly flexible molecular chain structure that can significantly improve the cycling performance of the lithium-ion battery.

[0220] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.

Claims

1. A polymer used in a battery monomer, wherein: The polymer is added to a first solvent at a first temperature to form a polymer system; The polymer system is allowed to stand for 8 hours at the first temperature and for ≥24 hours at the second temperature, and the first substance remains after the polymer system is filtered through a 200-mesh filter, and the first temperature is greater than the second temperature. The mass of the polymer is n, and its unit is g; the mass of the first substance is m, and its unit is g; the polymer and the first substance satisfy: 5≤m / n≤1000.

2. The polymer according to claim 1, wherein 10≤m / n≤1000; further optionally, 10≤m / n≤50.

3. The polymer according to claim 1 or 2, wherein The first solvent includes a cyclic carbonate solvent and / or a linear carbonate solvent; Optionally, the cyclic carbonate solvent includes one or more of ethylene carbonate EC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl carbonate VEC and dioctyl carbonate CC; Optionally, the linear carbonate solvent includes one or more of dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, diphenyl carbonate DPC, methyl allyl carbonate MAC and polycarbonate VA.

4. The polymer according to any one of claims 1 to 3, wherein The crystallinity of the polymer measured by differential scanning calorimetry is X C %,0<X C ≤30; The melting temperature of the polymer is Tm, the unit is °C, 0<Tm≤140.

5. The polymer according to any one of claims 1 to 4, wherein The glass transition temperature of the polymer is Tg, the unit of which is °C, -150≤Tg≤60.

6. The polymer according to any one of claims 1 to 5, wherein The polymer comprises at least one of the structural units represented by formula (I) to the structural units represented by formula (III), In formula (I) and formula (II), R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and at least one of R1, R2, R3 and R4 includes a fluorine atom; when substituted, the substituent includes a fluorine atom; Optionally, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C2 alkyl group or a substituted or unsubstituted C1-C2 alkoxy group; further optionally, R1, R2, R3 and R4 each independently include a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, a fluoromethyl group, a methoxy group or a perfluoromethoxy group; In formula (III), R5 includes a single bond, a substituted or unsubstituted C1-C3 alkyl group; when substituted, the substituent includes a fluorine atom; p is a positive integer selected from 1 to 3; n is a positive integer selected from 1,000 to 30,000.

7. The polymer according to any one of claims 1 to 6, wherein The polymer includes at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-11), 8. The polymer according to any one of claims 1 to 7, wherein The polymer further comprises at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-5), 9. The polymer according to any one of claims 1 to 8, wherein The polymer further comprises at least one of the structural units represented by formula (III-1) to the structural units represented by formula (III-3), 10. The polymer according to any one of claims 6 to 9, wherein n is a positive integer selected from 5000 to 20000; and / or The molecular weight of the polymer is 2×10 5 g / mol to 1.5×10 6 g / mol.

11. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector, wherein the positive electrode film layer comprises a positive electrode active material and a polymer, and the polymer comprises the polymer according to any one of claims 1 to 10.

12. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode film layer disposed on the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material and a polymer, and the polymer comprises the polymer according to any one of claims 1 to 10.

13. A battery cell, comprising a positive electrode sheet and a negative electrode sheet, wherein: The positive electrode sheet comprises the positive electrode sheet as claimed in claim 11; and / or The negative electrode plate comprises the negative electrode plate as claimed in claim 12.

14. A battery comprising the battery cell according to claim 13.

15. An electrical device comprising the battery cell according to claim 14.